The lost boys of Montauk : the true story of the Wind Blown, four men who vanished at sea, and the survivors they left behind - Fairbanks, Amanda M. (Gallery Books, 2021)
"In the tradition of the #1 New York Times bestseller (and Academy-Award nominated film) The Perfect Storm, and with a nod to Steven Gaines' dishy tell-all, Philistines at the Hedgerow, a riveting account of a fishing boat and its four young crewman lost at sea in 1984 off the coast of Montauk in eastern Long Island -- a "fishing town with a drinking problem," as the locals have it -- and the stunning repercussions of that loss for the families and friends of the four missing men and, indeed, the entire storied summer community of the Hamptons"--